The role of research in a technical assistance agency: the case of the ‘German Agency for Technical Co-operation’ - Horchler, Sonja; Mitra, Subrata Kumar; Sauerborn, Rainer (Health policy, 2004)
Technical assistance agencies have a sustainable impact on the health systems of the countries they are operating in. As well as policy-makers at the national level, technical assistance agencies see themselves confronted that their interventions should be based on evidence, usually meaning the results of research. This study has the aim to analyse role of research in the implementation of technical assistance. We sent a questionnaire to all health project managers of the ‘German Agency for Technical Co-operation’ and performed a qualitative case study in one of the health projects. Forty-seven of 80 (58.8%) of the questionnaires were completed and sent back. The managers considered publications of International Organisations (IOs), scientific articles and local research as most important for their work. The case study showed application problems in the daily work. Research use not only depends on the relevance of the data but also on analytical skills, linguistic barriers and technical access to research by the potential users. The role of knowledge and information management has to be clearly defined in an organisation of technical assistance. The specific needs at the different levels have to be analysed so that skills and resources can be allocated adequately.